A picture book of Harriet Tubman - Adler, David A, 1947-; Byrd, Samuel (New York : Holiday House, 1992)
Biography of the African-American woman who escaped from slavery to become famous as a conductor on the Underground Railroad.
Wilson's Children, October 2010.
School Library Journal, January 1996.
Booklist, February 2001.
Multicultural Review, November 2004.
4.3
3-6
Keywords: Tubman, Harriet, -- 1820?-1913 -- Juvenile literature; Tubman, Harriet, -- 1820?-1913.; Slaves -- United States -- Biography -- Juvenile literature; African Americans -- Biography -- Juvenile literature; Underground railroad -- Juvenile literature; Slavery -- United States -- Anti-slavery movements -- Juvenile literature; African Americans -- Biography; Slaves; Underground railroad; Slavery; African Americans -- Biography; Slaves -- Biography; Underground railroad